Strategies for Improving Foreign Language Skills of Primary School-Aged Children at Miracle Language Center, Narathiwat, Thailand - Ayu, Ayu; Sulistyowati, Sulistyowati; Mahama, Salmee (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Foreign language skills are often a problem due to declining interest while the demands of mastering foreign languages include the demands of the times and global competition. These skills are applied to elementary school-age children.  The purpose of this study is to describe how strategies to improve foreign language skills of elementary school-age children at Miracle Language Center, Narathiwat, Thailand. This research uses field research, namely qualitative-descriptive research design. The research informants consisted of teachers and students. Interviews with teachers to obtain general implementation information and with students to obtain information on the extent of foreign language acquisition at Miracle Language Center educational institutions. The method used is the Miles and Huberman (2014) approach of digging, reviewing data until obtaining saturated data, then all data is collected, data reduction, presenting data and the final step is making conclusions. The results in this study indicate that the strategy of improving children's language skills by providing English and Indonesian vocabulary with a vocabulary matching system as a basic understanding of language that is able to improve children's learning skills and enthusiasm due to the language environment in the Miracle Language Center institution, Thailand being an effective institution in supporting the ability to master foreign languages for children from an early age with a vulnerable 10-12 years.